Detection of pathogenic leptospira in water and soil from selected environment of Sarawak - Yong, Ya Fen. (Universiti Malaysia Sarawak (UNIMAS), 2015)
The Leptospira genus is tightly coiled spirochete from the Leptospiraceae family of the Spirochaetales order. Based on genotypic classification, 20 Leptospira species and over 300 serovars which are categorised into 20 serogroups have been recognized. Pathogenic Leptospira which are the causative agents of leptospirosis require hosts for survival and reproduction. Previous studies have reported the presence of pathogenic Leptospira from selected environment in Peninsular Malaysia. Since there is limited information about Leptospira in environments in Sarawak, therefore, this study is aimed to detect pathogenic Leptospira in water and soils from selected environment of Sarawak. A total of 175 water samples and 174 soil samples were collected from Kota Samarahan and Samunsam Wildlife Sanctuary of Sarawak. The samples were cultured in EMJH media supplemented with 5-fluorouracil for 30 days and later subjected to DNA extraction for peR targeting /ipL32 gene to confirm the pathogenic status of Leptospira. The OCCUITence of pathogenic Leptospira is higher in Kota Samarahan with 7.5% (18/240) samples were confirmed to be positive through peR analysis. Whereas, 4.6% (5/109) samples collected from Samunsam Wildlife Sanctuary exhibited positive leptospiral isolates. In conclusion, this study can provide important information about the occurrence ofpathogenic Leptospira in environments of Sara.wak for epidemiological study of leptospirosis in Malaysia.